Formulation design of oxcarbazepine fast-release tablets prepared by melt granulation technique - Patel, Nirav V; Chotai, Narendra P; Patel, Mayur P (Asian Journal of Pharmaceutics (AJP), 2014)
This work describes a melt granulation technique to improve the dissolution characteristics of a poorly water-soluble drug,oxcarbazepine. Melt granulation technique is a process by which pharmaceutical powders are efficiently agglomerated by a meltable binder.The advantage of this technique compared to conventional granulation is that no water or organic solvents are needed. Because there is no drying step, the process is less time consuming and uses less energy than wet granulation. In particular, the granules containing oxcarbazepine were prepared using polyethylene glycol (PEG) 4000 as a melting binder and lactose monohydrate as a hydrophilic filler.The potential of the intragranular addition of starch as a dissolution enhancer and a disintegrative agent was also evaluated. After analysis of their solid state was performed by means of x-ray powder diffraction (XRD), the granules were characterized from technological and dissolution point of view. The subsequent step comprised of the preparation and evaluation of the tablets, including the effect of the extragranular introduction of starch.Besides the remarkable enhancement of drug dissolution rate of the granulates in comparison to physical mixtures and pure drug, no significant differences were found between the dissolution profiles of the granulates containing lactose or starch.However, the difficult disintegration and bad dissolution performance of the tablets not containing intragranular starch so it is necessary to add disintegrant in the granulating mixture. Moreover, the extragranular addition of a small amount of starch gave rise to further amelioration of the disintegration and dissolution performances.